Upaya Pengelola Bank Sampah dalam Pengolahan Sampah - Rafli Alviansyah, Muhammad; Nurlaila, Nurlaila (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. Waste management is a big challenge for many countries around the world. To resolve this issue, the manager of the Waste Bank manager has become a more popular solution. The purpose in this study is to know the picture of what efforts are often done by the manager of the waste bank in processing of waste. The method used in this research is quantitative research method with descriptive approach and data collection techniques used, narrowed, interview and observation. The results of this study are: 1) In general, the average answer has a high level of understanding rat and is quite effective in the management of waste management in the Ciherang Village area; and 2) the community or members as well as manager of the Waste Bank in Ciherang Village has understood on aspects of knowledge, implementation and effort undertaken in garbage cooperation in the waste bank.